Evaluation of Contrast-Enhanced Ultrasound in Diagnosis of Acute Kidney Injury of Patients in Intensive Care Unit - Song Y; Mei J; Xu D; Ma Y (International Journal of General Medicine, 2023)
Ye Song,1 Jiangjun Mei,1 Dongwei Xu,2 Ying Ma1 1Department of Ultrasonography, Shanghai Pudong New Area Zhoupu Hospital, Shanghai University of Medicine & Health Sciences, Shanghai, 201318, People’s Republic of China; 2Department of Critical Care Medicine, Shanghai Pudong New Area Zhoupu Hospital, Shanghai University of Medicine & Health Sciences, Shanghai, People’s Republic of ChinaCorrespondence: Ye Song, Tel +86 13818086439, Email songye@tongji.edu.cnBackground: Ultrasound can assess renal perfusion, but its role in the evaluation of acute kidney injury (AKI) is still unclear. This prospective cohort study was to investigate the value of contrast-enhanced ultrasound (CEUS) in the evaluation of AKI in intensive care unit (ICU) patients.Methods: Fifty-eight patients were recruited from ICU between October 2019 and October 2020, and CEUS was used to monitor the renal microcirculation perfusion within 24h after admission. Parameters included rise time (RT), time to peak intensity (TTP), amplitude of peak intensity (PI), area under the curve (AUC), time from peak to one half (TP1/2) of renal cortex and medulla. Ultrasonographical findings, demographics, laboratory, etc were collected for further analysis.Results: There were 30 patients in the AKI group and 28 patients in the non-AKI group. The TTP, PI, TP1/2 of the cortex and the RT, TTP, TP1/2 of the medulla in the AKI group were significantly longer than in the non-AKI group (P < 0.05);. The TTP (OR = 1.261, 95% CI: 1.083– 1.468, P = 0.003) (AUCs 0.733, Sen% 83.3, Spe%57.1), TP1/2 (OR = 1.079, 95% CI: 1.009– 1.155, P = 0.027) (AUCs 0.658, Sen% 76.7, Spe%50.0) of the cortex and RT (OR = 1.453, 95% CI: 1.051– 2.011, P = 0.024) (AUCs 0.686, Sen% 43.3, Spe%92.9) of the medulla were related to the AKI. Eight new-onset AKI cases occurred in the non-AKI group within 7 days, the RT, TTP, TP1/2 of the cortex and medulla were significantly longer in the new-onset AKI group than in the non-AKI group (P < 0.05), but serum creatinine and blood urea nitrogen were no differences between groups (P > 0.05).Conclusion: This study indicates CEUS can assess the renal perfusion in AKI. TTP and TP1/2 of the cortex and RT of the medulla can aid the diagnosis of AKI in ICU patients.Keywords: contrast-enhanced ultrasound, acute kidney injury, intensive care unit